Vergleich von Disambiguierungsansätzen bei Anforderungsbeschreibungen - Vollmers, Daniel

Market-Specific Service Compositions: Specification and Matching - Arifulina, Svetlana; Platenius, Marie Christin; Mohr, Felix; Engels, Gregor; Schäfer, Wilhelm (Proceedings of the IEEE 11th World Congress on Services (SERVICES), Visionary Track: Service Composition for the Future Internet)
The Collaborative Research Centre "On-The-Fly Computing" works on foundations and principles for the vision of the Future Internet. It proposes the paradigm of On-The-Fly Computing, which tackles emerging worldwide service markets. In these markets, service providers trade software, platform, and infrastructure as a service. Service requesters state requirements on services. To satisfy these requirements, the new role of brokers, who are (human) actors building service compositions on the fly, is introduced. Brokers have to specify service compositions formally and comprehensively using a domain-specific language (DSL), and to use service matching for the discovery of the constituent services available in the market. The broker's choice of the DSL and matching approaches influences her success of building compositions as distinctive properties of different service markets play a significant role. In this paper, we propose a new approach of engineering a situation-specific DSL by customizing a comprehensive, modular DSL and its matching for given service market properties. This enables the broker to create market-specific composition specifications and to perform market-specific service matching. As a result, the broker builds service compositions satisfying the requester's requirements more accurately. We evaluated the presented concepts using case studies in service markets for tourism and university management.

Fuzzy Matching von Vor- und Nachbedingungen in Servicespezikationen - Börding, Paul

Filtering Reviews by Random Individual Error - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Stuß, Valentina (Proceedings of the 28th International Conference on Industrial, Engineering and Other Applications of Applied Intelligent Systems (IEA/AIE 2015))
Opinion mining from physician rating websites depends on the quality of the extracted information. Sometimes reviews are user-error prone and the assigned stars or grades contradict the associated content. We therefore aim at detecting random individual error within reviews. Such errors comprise the disagreement in polarity of review texts and the respective ratings. The challenges that thereby arise are (1) the content and sentiment analysis of the review texts and (2) the removal of the random individual errors contained therein. To solve these tasks, we assign polarities to automatically recognized opinion phrases in reviews and then check for divergence in rating and text polarity. The novelty of our approach is that we improve user-generated data quality by excluding error-prone reviews on German physician websites from average ratings.

Ein Framework für Fuzzy Service Matching basierend auf Fuzzy Sets - Neumann, Conrad

Design of an Evaluation Strategy for Fuzzy Service Matching - Bruns, Melanie

Comprehensive Service Matching with MatchBox - Börding, Paul; Bruns, Melanie; Platenius, Marie Christin (10th Joint Meeting of the European Software Engineering Conference and the ACM SIGSOFT Symposium on the Foundations of Software Engineering (ESEC/FSE'15))
Nowadays, many service providers offer software components in the form of Software as a Service. Requesters that want to discover those services in order to use or to integrate them, need to find out which service satisfies their requirements best. For this purpose, service matching approaches determine how well the specifications of provided services satisfy their requirements (including structural, behavioral, and non-functional requirements). In this paper, we describe the tool-suite MatchBox that allows the integration of existing service matchers and their combination as part of flexibly configurable matching processes. Taking requirements and service specifications as an input, MatchBox is able to execute such matching processes and deliver rich matching results. In contrast to related tools, MatchBox allows users to take into account many different kinds of requirements, while it also provides the flexibility to control the matching process in many different ways.

Automatic Service Discovery and Composition for heterogeneous service partners - Huma, Zille

MatchBox: A Framework for Dynamic Configuration of Service Matching Processes - Platenius, Marie Christin; Arifulina, Svetlana; Schäfer, Wilhelm (Proceedings of the 18th International ACM Sigsoft Symposium on Component-Based Software Engineering (CBSE'15))
Service discovery in global software markets is performed by brokers who act as intermediaries between service consumers and service providers.In order to discover services, brokers apply service matching for determining whether the specification of a provided service satisfies the consumer's requirements.Brokers can already choose between a lot of different service matching approaches considering different service properties (structural, behavioral, and non-functional properties).Different matching approaches can be combined into configurable matching processes leading to a high matching quality (e.g., accurate matching results). However, this combination and configuration is a manual procedure and has to be repeated for different consumers' or market requirements regarding matching quality. In this paper, we propose our framework MatchBox, which supports a broker in reusing existing matching approaches and combining them in a model-driven way based on a reconfigurable model of the matching process.Using this reconfigurable model, MatchBox takes care of control and data flow between matching approaches and executes the modeled processes automatically.As a case study, we integrated eleven matchers into MatchBox to demonstrate that it remains flexibility and reduces effort for a broker at the same time.

What did you mean? Facing the Challenges of User-generated Software Requirements - Geierhos, Michaela; Schulze, Sabine; Bäumer, Frederik Simon (Proceedings of the 7th International Conference on Agents and Artificial Intelligence (ICAART), Special Session on Partiality, Underspecification, and Natural Language Processing (PUaNLP 2015))
Existing approaches towards service composition demand requirements of the customers in terms of service templates, service query profiles, or partial process models. However, addressed non-expert customers may be unable to fill-in the slots of service templates as requested or to describe, for example, pre- and postconditions, or even have difficulties in formalizing their requirements. Thus, our idea is to provide non-experts with suggestions how to complete or clarify their requirement descriptions written in natural language. Two main issues have to be tackled: (1) partial or full inability (incapacity) of non-experts to specify their requirements correctly in formal and precise ways, and (2) problems in text analysis due to fuzziness in natural language. We present ideas how to face these challenges by means of requirement disambiguation and completion. Therefore, we conduct ontology-based requirement extraction and similarity retrieval based on requirement descriptions that are gathered from App marketplaces. The innovative aspect of our work is that we support users without expert knowledge in writing their requirements by simultaneously resolving ambiguity, vagueness, and underspecification in natural language.

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Brangewitz, Sonja; Jungmann, Alexander; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the 6th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
One future goal of service-oriented computing is to realize global markets of composed services. On such markets, service providers offer services that can be flexibly combined with each other. However, most often, market participants are not able to individually estimate the quality of traded services in advance. As a consequence, even potentially profitable transactions between customers and providers might not take place. In the worst case, this can induce a market failure. To overcome this problem, we propose the incorporation of reputation information as an indicator for expected service quality. We address On-The-Fly Computing as a representative environment of markets of composed services. In this environment, customers provide feedback on transactions. We present a conceptual design of a reputation system which collects and processes user feedback, and provides it to participants in the market. Our contribution includes the identification of requirements for such a reputation system from a technical and an economic perspective. Based on these requirements, we propose a flexible solution that facilitates the incorporation of reputation information into markets of composed services while simultaneously preserving privacy of customers who provide feedback. The requirements we formulate in this paper have just been partially met in literature. An integrated approach, however, has not been addressed yet.

SeSAME: Modeling and Analyzing High-Quality Service Compositions - Arifulina, Svetlana; Becker, Matthias; Platenius, Marie Christin; Walther, Sven (Proceedings of the 29th IEEE/ACM International Conference on Automated Software Engineering (ASE 2014))
Today, software components are traded on markets in form of services. These services can also be service compositions consisting of several services. If a software architect wants to provide such a service composition in the market for trade, she needs to perform several tasks: she needs to model the composition, to discover existing services to be part of that composition, and to analyze the composition's functional correctness as well as its quality, e.g., performance. Up to now, the architect needed to find and use different tools for these tasks. Typically, these tools are not interoperable with each other. We provide the tool SeSAME that supports a software architect in all of these tasks. SeSAME is an integrated Eclipse-based tool-suite providing a comprehensive service specification language to model service compositions and existing services. Furthermore, it includes modules for service matching, functional analysis, and non-functional analysis. SeSAME is the first tool that integrates all these tasks into one tool-suite and, thereby, provides holistic support for trading software services. Thus, it contributes to a software provider's market success.

Security and Privacy Challenges in On-The-Fly Computing - Petrlic, Ronald; Jungmann, Alexander; Platenius, Marie Christin; Schäfer, Wilhelm; Sorge, Christoph (Tagungsband der 4. Konferenz Software-Technologien und -Prozesse (STeP 2014))
On-The-Fly (OTF) Computing constitutes an approach towards highly dynamic and individualized software markets. Based on service-oriented computing, OTF Computing is about realizing global markets of services that can be flexibly combined. We report on our current research activities, the security and privacy implications thereof, and our approaches to tackle the challenges. Furthermore, we discuss how the security and privacy challenges are addressed in research projects similar to OTF Computing.

Reengineering Component-Based Software Systems with Archimetrix - von Detten, Markus; Platenius, Marie Christin; Becker, Steffen (Journal of Software and Systems Modeling)
Many software development, planning, or analysis tasks require an up-to-date software architecture documentation. However, this documentation is often outdated, unavailable, or at least not available as a formal model which analysis tools could use. Reverse engineering methods try to fill this gap. However, as they process the system’s source code, they are easily misled by design deficiencies (e.g., violations of component encapsulation) which leaked into the code during the system’s evolution. Despite the high impact of design deficiencies on the quality of the resulting software architecture models, none of the surveyed related works is able to cope with them during the reverse engineering process. Therefore, we have developed the Archimetrix approach which semi-automatically recovers the system’s concrete architecture in a formal model while simultaneously detecting and removing design deficiencies. We have validated Archi metrix on a case-study system and two implementation variants of the CoCoME benchmark system. Results show that the removal of relevant design deficiencies leads to an architecture model which more closely matches the system’s conceptual architecture.

On-the-Fly Computing: Automatic Service Discovery and Composition in Heterogeneous Domains - Huma, Zille; Gerth, Christian; Engels, Gregor (Computer Science - Research and Development)
In software markets of the future, customer-specific software will be developed on demand based on distributed software and hardware services. Based on a customer-specific request, available service offers have to be discovered and composed into sophisticated IT services that fulfill the customer's request.A prerequisite of this vision are rich service descriptions, which comprise structural as well as behavioral aspects of the services, otherwise an accurate service discovery and composition is not possible. However, automatic matching of service requests and offers specified in rich service descriptions for the purpose of service discovery is a complex task, due to the multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different specification languages, different underlying ontologies, or different levels of granularity in the specification itself.In this article, we present a comprehensive approach for service discovery and composition, which overcomes the underlying heterogeneity of the service partners. Based on a realistic case study of our industrial partner from the e-tourism domain, we first introduce an automatic matching mechanism for service requests and offers specified in a rich service description language. In addition, we propose an automatic service composition approach, which determines possible service compositions by composing the service protocols through a composition strategy based on labeled transition systems.

Combination of Service Matching Steps in Consideration of Efficiency and Fuzziness - Gao, Yuan

Cloud Computing Reduces Uncertainties in Quality-of-Service Matching! - Becker, Matthias; Platenius, Marie Christin; Becker, Steffen (Proceedings of the 2nd International Workshop on Cloud Service Brokerage (CSB))
Cloud computing resulted in a continuously growing number of provided software services to be used by consumers. Brokers discover services that fit best to consumers' requirements by matching Qualityof-Service (QoS) properties. In order to negotiate Service-Level Agreements (SLAs), a provider has to determine the provided QoS based on QoS analyses. However, the risk for the provider to violate the SLA is high as the service's actual quality can deviate from the specified QoS due to uncertainties that occur during the provider's quality analysis. In this paper, we discuss current software engineering paradigms like cloud computing and service-oriented computing with respect to the amount of uncertainty they induce into service matching and SLA negotiations. As a result, we explain, why cloud computing reduces such uncertainties.

Normalizing Heterogeneous Service Description Models with Generated QVT Transformations - Schwichtenberg, Simon; Gerth, Christian; Huma, Zille; Engels, Gregor (Proceedings of the 10th European Conference on Modelling Foundations and Applications (ECMFA))
Service Oriented Architectures (SOAs) enable the reuse and substitution of software services to develop highly flexible software systems. To benefit from the growing plethora of available services, sophisticated service discovery approaches are needed that bring service requests and offers together. Such approaches rely on rich service descriptions, which specify also the behavior of provided/requested services, e.g., by pre- and postconditions of operations. As a base for the specification a data schema is used, which specifies the used data types and their relations. However, data schemas are typically heterogeneous wrt. their structure and terminology, since they are created individually in their diverse application contexts. As a consequence the behavioral models that are typed over the heterogeneous data schemas, cannot be compared directly. In this paper, we present an holistic approach to normalize rich service description models to enable behavior-aware service discovery. The approach consists of a matching algorithm that helps to resolve structural and terminological heterogeneity in data schemas by exploiting domain-specific background ontologies. The resulting data schema mappings are represented in terms of Query View Transformation (QVT) relations that even reflect complex n:m correspondences. By executing the transformation, behavioral models are automatically normalized, which is a prerequisite for a behavior-aware operation matching.

Modeling and Matching of Reputation of Services in On-The-Fly Computing - Bano, Dorina

Measuring Transformation-induced Uncertainty in Service Matching: A Feasibility Study - Bunse, Mirko